Selected papers on soil mechanics - Skempton, A. W. (Thomas Telford, 1984)
A selection of papers by Professor A.W. Skempton, aiming to show his breadth of achievement in the field of soil mechanics. The chosen papers are reproduced chronologically, most of them falling into three subject groups: soil properties, stability of slopes, and foundations.